Karakteristik Sampah dan Produk Kompos dari Kawasan Perumahan: Indonesia - Widayanti, Rini; Siswoyo, Eko (Teknik Lingkungan Universitas Islam Indonesia, 2025)
Waste management has become a serious problem across all urban areas in Indonesia, where the main issue is the lack of treatment at the source. One of the best solutions to process waste is at the source, for example, through composting. This study aims to design a compost reactor and analyze the nitrogen (N), phosphate (P), potassium (K), and C/N ratio of the composting products. In this study, the material used was household organic waste from the Griya Taman Asri Housing Residence Block F, which had been sorted into three categories: organic, inorganic, and non-3R. The composting process was carried out aerobically with the addition of EM4 starter, using a plastic drum reactor with holes on each side. Inside the drum, a pipe with holes was installed, while a filter and tap were placed at the bottom. During fermentation, temperature and pH were measured every 3 days. After calculating the amount of waste generated, a reactor with a capacity of 60 liters was produced. The N content was 1.821%, P was 1.131%, K was 3.516%, and the C/N ratio was 19.97, with a compost maturation period of 22 days. Based on the N, P, and K content of the compost product, compared with the N, P, and K content standards of the SNI compost quality standard and market compost quality standards, the compost produced in this study is considered of good quality.